Analysis Of Compensation, Leadership, And Co-Workers On Job Satisfaction Of Honorary Employees Of Langkat District Cooperative Office - Emi Wakhyuni; Ikhah Malikhah; Abdul Ghafur Azhar (International Journal of Management, Economic and Accounting, 2023)
The purpose of this study is to investigate the influence of compensation, leadership, and co-workers on the job satisfaction of honorer employees of the Langkat District Cooperative Office. The population of this study is all honorer employees of the Langkat District Cooperative Office, totaling 65 employees. The number of samples taken was 65 respondents. The sampling technique used was saturated sampling. This study was conducted in 2022. This study uses quantitative data that is processed with SPSS 24.0 using multiple linear regression methods. The results of the study show that compensation, leadership, and co-workers have a positive and significant influence on the job satisfaction of honorer employees of the Langkat District Cooperative Office, both partially and simultaneously. The results of the t test (partial) show that compensation has a regression value of 0.554, tcount value = 5.309 and significant = 0.000. Leadership has a regression value of 0.335, tcount value = 3.140 and significant = 0.003. Co-workers have a regression value of 0.269, tcount value = 2.648 and significant = 0.010. The results of the F test (simultaneously) show Fcount = 300.948 and significant = 0.000. Compensation becomes the most dominant variable influencing job satisfaction with the largest tcount value, which is 5.309. 93.4% of job satisfaction can be explained and obtained from compensation, leadership, and co-workers, while the remaining by other factors. Job satisfaction has a very strong relationship with compensation, leadership, and co-workers.